Systemic brain dissemination of glioblastoma requires transdifferentiation into endothelial-like cells via TGF-β-ALK1-Smad1/5 signaling - Thomas M.B. Ware; Adilson Fonseca Teixeira; Josephine Iaria; Rodney B. Luwor; Hong-Jian Zhu (Neoplasia: An International Journal for Oncology Research)
Glioblastoma is the most aggressive type of brain cancer, but treatment improvements for glioblastoma patients remain stagnated for over 20 years. This is despite the large number of clinical trials that have attempted to replicate the success of therapeutics developed for other cancer types. This discrepancy highlights the urgent need to decipher the unique biology of glioblastomas. Here, we show that glioblastoma tumour cells are highly plastic, integrating into blood vessel walls to disseminate throughout the brain. This relies on the transdifferentiation of glioblastoma tumor cells into endothelial-like cells in a process we termed endothelialisation. Mechanistically, in addition to TGF-β-ALK5-Smad2/3 signaling, glioblastoma tumour cells also activate TGF-β-ALK1-Smad1/5 signaling – a mechanism previously thought to be limited to endothelial cells. Consequently, therapeutic targeting of TGF-β-ALK1-Smad1/5 activity impaired endothelialisation-driven glioblastoma progression. This study identifies a previously unknown component of glioblastoma biology and establishes a therapeutic approach to reduce the progression of this disease.